Prevalence of subjective impairments of the sense of smell and taste in employees of retirement and nursing homes during SARS‐CoV‐2 pandemic - Frederic Jungbauer; Lena Huber; Anne Lammert; Sonja Ludwig; Nicole Rotter; Lena Zaubitzer; Angela Schell (Wiley, 2022)
Abstract Aim To investigate the usability of querying subjective impairments of the sense of smell and taste in order to improve pre‐test probability in testing for SARS‐CoV‐2. To achieve this, exploring the prevalence of these restrictions in the COVID‐19‐negative population, as well as nasal co‐symptoms. Design A cross‐sectional study was carried out as part of the secondary prophylaxis, following the STROBE guidelines of the EQUATOR network. Methods In total, 1,734 employees of retirement and nursing homes were tested for COVID‐19 and asked for subjective reduction or loss in the sense of smell and taste, furthermore about nasal co‐symptoms such as nasal obstruction and rhinorrhoea. Results All employees tested negative for COVID‐19. Subjective hyposmia and hypogeusia rarely occurred and were usually accompanied by other nasal symptoms such as nasal obstruction. Querying subjective hyposmia/anosmia or hypogeusia/ageusia appears to be a useful anamnestic instrument for the clinical assessment of the probability of SARS‐CoV‐2 infection.